Unwinding financial sector interventions preconditions and practical considerations - Das, Udaibir S.; Papaioannou, Michael G. (International Monetary Fund, 2010)
As the financial crisis abates, governments are faced with the challenge of balancing the withdrawal of fiscal support with reestablishing sound public finances and sustainable growth. This volume presents papers from an IMF-sponsored conference of senior policymakers, academics, and senior representatives of the private sector on unwinding public interventions initiated during the crisis. There was broad agreement that the main goal of any strategy for unwinding such interventions should be to create price stability, fiscal sustainability, and a new economic landscape that is much safer than currently exists. Different perspectives on the timing and sequence of the exit process are presented and some guiding principles for exit strategies are discussed. Policy objectives, unwinding public support to banks, and dealing with risky assets purchased by central banks are among topics discussed in detail. The volume also presents views on what the new financial landscape will look like.--Publisher's description.